A lethal model of Leptospira infection in hamster nasal mucosa. - Jiaqi Wang; Wenlong Zhang; Zhao Jin; Yue Ding; Shilei Zhang; Dianjun Wu; Yongguo Cao (Public Library of Science (PLoS), 2022)
Leptospirosis is a fatal zoonosis caused by contact between skin or a mucosal surface and contaminated soil or water. Hamsters were infected by intraperitoneal injection fto establish experimental leptospirosis, which is not a natural route of infection. There are no reports of nasal mucosal infection in hamsters. In this study, infection of the nasal mucosa was performed to establish a model of natural infection. Both methods of infection can cause lethal models with similar symptoms in the later stages of infection, such as weight loss, blood concentration, increased neutrophils (GRAN), and decreased lymphocytes (LYM) in the blood, severe organ damage and liver function obstruction. The burden of Leptospira in the organs and blood was lower in the mucosal inoculation groups at 1 day after infection. However, mucosal infection induced a higher Leptospira burden in urine than intraperitoneal infection in the late stages of infection. After nasal mucosal infection, antibody levels were higher and lasted longer. These results indicated that the route of nasal mucosal infection is a good choice for studying leptospirosis in hamsters.